1992
DOI: 10.1016/0014-5793(92)80701-h
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II directly induces follicle rupture and oocyte maturation in the rabbit

Abstract: To investigate the possible direct involvement ofangiotensin II (Ang II) in ovulation and oocyte maturation, Ang II ill lOOor IOyg was administered at 2-h intervals in the in-vitro perfused rabbit ovaries. The addition of Ang II in the pcrfusate induced ovulation in vhro in the absence of gonadotropin, while ovulation did not occur in any contralaleral control ovaries. I-Iowcver, the ovulatory eflicicncy in the Ang II-trcatcd ovaries was signiiicantly lower than in hCG-treated ovaries. Ang II signilicantly sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 21 publications
3
56
0
2
Order By: Relevance
“…Captopril (an ACE inhibitor) did not inhibit ovulation in rats (Daud et al 1990). In contrast, the Ang II type 2 receptor (AGTR2) blocker inhibited ovulation in the rabbit and bovine (Yoshimura et al 1992, Ferreira et al 2007, suggesting the presence of an alternative enzymatic route to the synthesis of ovarian Ang II. The members of plasminogen activator (PA) family, cathepsin D and chymase, are enzyme candidates to convert Ang I into the octapeptide Ang II (for review see Paul et al (2006)).…”
Section: Ovarian Rasmentioning
confidence: 95%
See 1 more Smart Citation
“…Captopril (an ACE inhibitor) did not inhibit ovulation in rats (Daud et al 1990). In contrast, the Ang II type 2 receptor (AGTR2) blocker inhibited ovulation in the rabbit and bovine (Yoshimura et al 1992, Ferreira et al 2007, suggesting the presence of an alternative enzymatic route to the synthesis of ovarian Ang II. The members of plasminogen activator (PA) family, cathepsin D and chymase, are enzyme candidates to convert Ang I into the octapeptide Ang II (for review see Paul et al (2006)).…”
Section: Ovarian Rasmentioning
confidence: 95%
“…Ang II is capable of inducing ovulation in rabbits even in the absence of gonadotropins (Kuo et al 1991, Yoshimura et al 1992. The effect of Ang II during ovulation is mediated, at least in part, by PGs.…”
Section: Ang II Signaling and Receptors Near Ovulationmentioning
confidence: 99%
“…In cows, the AngII receptor type 2 is present in the dominant follicle (Schauser et al 2001), and its mRNA expression was positively correlated with estradiol production (Portela et al 2006). In perfused rabbit ovaries, the ovulation and the meiosis resumption induced by hCG are blocked by saralasin (1-sarcosine-8-alanine-5-isoleucine-AngII, a competitive AngII antagonist; Yoshimura et al 1992). In contrast, Kuo et al (1991) reported that saralasin inhibited ovulation without affecting oocyte nuclear maturation in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the ovary has a local renin-angiotensin system, in which Ang II plays a crucial role in the processes of ovulation and oocyte maturation (Yoshimura et al, 1992). Here, we show that Ang II generates ion currents in isolated FCs in culture.…”
Section: Discussionmentioning
confidence: 55%